Slip detection methods and slip direction estimation on Quadruped Robots - Carvalho, Paulo Teixeira Vale de; Medeiros, Vivian Suzano; Meggiolaro, Marco Antonio (Anais Estendidos do Simpósio Brasileiro de Robótica e Simpósio Latino-Americano de Robótica (SBR/LARS), 2025)
Quadruped robots are mobile robots inspired by the locomotion of animals. Although widely studied, challenges such as slip events remain significant. This work compares existing proprioceptive slip detection methods and evaluates a strategy for reducing undesirable detections. A slip direction estimation method is proposed for calculating a filtered slip angle to assess slip behavior and explore its potential as a criterion for slip intensity. To validate the approach, simulations and experiments are conducted using the Go1 robot. Results include a quantitative evaluation of slip detection methods based on the friction cone model, demonstrating consistent outcomes between simulation and experimental data, as well as a correlation between slip angle and slip intensity.